Electronic and mechanical modification of single-walled carbon nanotubes by binding to porphyrin oligomers. - Stranks, S; Sprafke, J; Anderson, H; Nicholas, R (2011)
We report on the noncovalent binding of conjugated porphyrin oligomers to small diameter single-walled carbon nanotubes (SWNTs) and highlight two remarkable observations. First, the binding of the oligomers to SWNTs is so strong that it induces mechanical strain on the nanotubes in solution. The magnitudes of the strains are comparable to those found in solid-state studies. Comparable strains are not observed in any other SWNT-supramolecular complexes. Second, large decreases in polymer band gap with increasing length of the oligomer lead to the formation of a type-II heterojunction between long chain oligomers and small-diameter nanotubes. This is demonstrated by the observation of enhanced red-shifts for the nanotube interband transitions. These complexes offer considerable promise for photovoltaic devices.